Exploring The Qur’anic Narrative’s Punishment of Lūṭ’s Tribe: A Comparative Study of the Similarities Between Their Sins and Suffering - Fauzan, Muhammad Nuril (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2024)
This article explores the complex relationship between the wicked actions of Lūṭ’s community, as described in the Qur’an, and the particular type of retribution, known as ‘adhāb, that they experienced. The study used a qualitative research approach to thoroughly examine the Qur’ānic passages, aiming to reveal subtle connections between crimes and divine punishment. This research enhances comprehension of the concept of divine justice as depicted in the Qur’an by utilizing the theoretical framework of the theory of retribution, provided in a thematical explanation. The inquiry delves into the causality of the ‘adhāb as an effect of human transgressions, and in the study of Lūṭ’s narrative, there are various torments bestowed. The findings not only reveal historical and moral lessons embedded in the account of Lūṭ’s tribe but also offer a methodological framework for examining comparable narratives in the Qur’ān. This study seeks to prompt debates on the deep correlations between human behavior and divine repercussions, enhancing understanding of Islamic scriptures’ ethical and spiritual lessons.